Introduction to asepsis & sterile technique - Price, Paul; Association of Surgical Technologists (Englewood, Co. : Association of Surgical Technologists Presents, 2001)
Explains and demonstrates the basic principles of modern asepsis and visually defines the operating suite, ventilating system, OR furniture, hand washing, surgical attire, scrubbing, gowning, gloving and basic skills for maintaining a sterile field
Section 1. Principles of asepsis -- Section 2. Preliminary information -- Section 3. Basic skills
Production & post-production, Randy Holman - RH Productions ; producer, Karen Ludwig ; director, Paul Price ; author, Teri Junge.
VHS
Keywords: Asepsis; Operating rooms; Protective clothing